O papel do pai na fobia e na neurose obsessiva: o Pequeno Hans e o Homem dos ratos em Freud e em Lacan - Carvalho, Evelyn Benevides (2006)
This work aims at thinking upon the actions of the father (here understood as father in reality) in his possible contribution in leading the son to an obsessive neurosis or phobia from the relationships that happen in the context of the Oedipal triangulation. As neurosis is a defense strategy in face of castration, which particularities in the desiring relationships could lead to one typical form of defense or another? If the obsessive conflict unfolds eminently in the level of thought and the phobic in the level of reality (in the relationship with the phobic object), what could generate this difference? Aiming at clarifying some aspects of the role of the real father in structuring the child’s neurosis, it is necessary to observe the very development of the paternal function in its real, symbolic and imaginary levels; the relationship of the father with several other elements of the family’s dynamics: the desiring dynamics in the parental couple, the way that each of them relates to the law, the elements that interfere in those relationships, how the circulation of the phallus takes place in each case, among others. We have decided to carry out a bibliographical research and selected the clinical cases ‘Little Hans’ and ‘Rat Man’ as the fundamental basis of our discussion, as we believe that the analysis of what is most particular can unveil universal aspects of each structure. Furthermore, we start from the principle that the Freudian text is not exhausted in its possibilities of surprising us and offering new questions. We utilize the Lacanian contribution (in an initial moment of his teachings) and another reading of those clinical cases. Authors such as Jerusalinsk, Julien, Dor, Ambertín, Gazzola, Melman, among others, are also summoned to enrich our discussion. We investigate the similarities and the differences in the way that the father, in each case, has performed his function, which is dual: restrainer and model of identification, as well as his possible consequences on the subject, the subject’s way of dealing with desire and castration. In phobia, to delimitate and allay the anguish, the subject needs to resort to the phobic object as a supplement to the paternal function that appears in an insufficient form in the relationship mother-son. This object comes to provide limits to the subject’s world, to demarcate points of danger and to serve as support to a series of symbolic-imaginary elaborations which can render possible a meaningful change, as in Hans’ case, in which there was an analytical intervention. In the obsessive neurosis, there is a subject tormented by recurring thoughts and driven to rituals as attempts of protection in face of danger, permanently in conflict with the phallic instance, oscillating between the wish of transgressing it and the devoted submission. A law that, for the obsessive has become difficult to elaborate, perhaps because it has been put in excessive or ambiguous way in the desiring context of the child. In the obsessive, the passage from the ‘being’ to the ‘having’ becomes more problematic due to the message of maternal dissatisfaction in relation to the husband. That makes it difficult to the subject to give up on his imaginary phallic identification, while at the same time he recognizes the existence and fears the instance of the law. As to the phobic, it can be that he has been more at the mercy of maternal desire, without a third instance to protect him of the risk of annihilation. ‘Killing (the father) or dying’ is the obsessive’s impasse. ‘Escaping (the maternal pleasure) is the phobic’s effort. This way, we attempt to bring our contributions, to recognize paradox and leave unanswered some questions that arise along the process and that can serve as a starting point to future research.